Measuring the effects of strategic capability, entrepreneurial orientation, servant leadership, and assistive technology on success of visually impaired leaders - Harziah, Khalid Yunus (2021)
The objective of this study is to examine the effect of strategic capability, entrepreneurial orientation and servant leadership on the success of visually impaired leaders in Malaysia. Additionally, this study also examined the moderating effect of assistive technology on the relationship between strategic capability, entrepreneurial orientation, servant leadership and success of visually impaired leaders. A theoretical framework was developed based on existing literature. The data was collected through an online survey by sending a link of questionnaires via WhatsApp to all visually impaired leaders in Malaysia. This study used a census survey to gather data. Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the study's hypotheses. The results provide support to few of the hypothesized relationships for the study. Specifically, strategic capability and entrepreneurial orientation significantly affect the success of visually impaired leaders while servant leadership is not affected. Furthermore, the result indicates that all three hypotheses are not significant due to low statistical power and assistive technology, besides moderation being quite new in leadership studies. Therefore, the significant effect of strategic capability and entrepreneurial orientation on the success of visually impaired leaders suggest that the variables are important in relation to the success of a leader. Assistive technology statistically is not significant but the results of focus group discussions show it is very important and significantly affects their daily lives. The outcome of this study provides significant contributions to both leaders and researchers for further understanding of what factors affect the success of a visually impaired leader in an organization. Hence, a leader should be encouraged to apply strategic capability and act like an entrepreneur to be a success leader. Contributions, limitations, implications and necessary suggestions for new areas of research are recommended and discussed in this research.